On the gelation of humins: from transient to covalent networks. Issue 15 (30th March 2023) - Cerdan, Kenneth; Gandara-Loe, Jesus; Arnauts, Giel; Vangramberen, Vedran; Ginzburg, Anton; Ameloot, Rob; Koos, Erin; Van Puyvelde, Peter
Abstract : Humins' gel structure combines physical and chemical crosslinks, with temperature dictating their properties. A change from a supramolecular to a covalently crosslinked network is observed, and the resulting stage of polymerization greatly influences material properties. Abstract : Humins are a by-product of many acid-catalyzed biorefinery processes converting polysaccharides into platform chemicals. The valorization of humin residue to increase the profit of biorefinery operations and reduce waste is a field that is growing interest as the production of humins continues to increase. This includes their valorization in materials science. For successful processing of humin-based materials, this study aims to understand the thermal polymerization mechanisms of humins from a rheological perspective. Thermal crosslinking of raw humins leads to an increase in their molecular weight, which in turn leads to the formation of a gel. Humin's gels structure combines physical (thermally reversible) and chemical (thermally irreversible) crosslinks, and temperature plays an essential role in the crosslink density and the gel properties. High temperatures delay the formation of a gel due to the scission of physicochemical interactions, drastically decreasing their viscosity, whereas upon cooling a stronger gel is formed combining the recovered physicochemical bonds and the newly created chemical crosslinks. Thus, a transition from a supramolecular network to a covalently crosslinked network is observed, and properties such as the elasticity or reprocessability of humin gels are influenced by the stage of polymerization.